2016
DOI: 10.1080/08952841.2016.1187536
|View full text |Cite
|
Sign up to set email alerts
|

Domestic helpers as frontline workers in China’s home-based elder care: A systematic review

Abstract: We conducted a systematic review of the existing empirical studies focusing on Chinese domestic helpers in mainland China and foreign domestic helpers in Hong Kong who provide care for community-dwelling older adults. There are very limited studies specifically focusing on this population. The findings synthesized domestic helpers' characteristics, acknowledged their contributions to elder care in China, and showed multiple challenges facing them, such as issues related to their physical health and emotional w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 24 publications
3
24
1
1
Order By: Relevance
“…The proportion of the population aged 65 years and older is estimated to reach 22.6% by 2040, double that in 2010 (9%) [2]. In addition, older adults are at high risk for chronic diseases and become functionally disabled [3]. The increase in the number of elderly people, the increase in life expectancy and the decline in fertility rate have aggravated the overall burden to society to care for the aged.…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of the population aged 65 years and older is estimated to reach 22.6% by 2040, double that in 2010 (9%) [2]. In addition, older adults are at high risk for chronic diseases and become functionally disabled [3]. The increase in the number of elderly people, the increase in life expectancy and the decline in fertility rate have aggravated the overall burden to society to care for the aged.…”
Section: Introductionmentioning
confidence: 99%
“…Global societal changes, such as low birth rates, increasing longevity, and changing family structures, have led to an increasing global trend of shifting the task of caring for older people in the community from family members to live-in migrant care workers (MCWs) [4–6]. This is happening in places such as Asia [7, 8], Canada [9], and in many European nations [1013]. The Hong Kong Special Administrative Region (hereafter, Hong Kong) is an affluent but ageing city located in the southern part of China.…”
Section: Introductionmentioning
confidence: 99%
“…In a systematic review conducted in China, 50% of live-in workers stated that they found it difficult to manage their negative emotions in interpersonal interactions [7]. Common stressors that trigger their negative emotions included the renewal of their employment contract and abusive behavior by employers, such as physical and verbal abuse, sexual harassment, and economic exploitation [7, 28]. For example, if an employer or a live-in MCW terminates an employment contract in Hong Kong, the live-in MCW has to leave Hong Kong within two weeks if s/he cannot start a new employment contract within those weeks.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the above caregiver health issues, several international agreements and conventions were drafted by the WHO and Alzheimer's Disease International (ADI), and some countries also have policies protecting the rights of caregivers, such as the 10/66 'Helping Carers to Care' train-the-trainer intervention in ADI [24], a national strategy for carers and Care Act in the UK [25][26][27][28], and the national dementia strategies in Australia. However, most countries/ regions still do not have long-term care (LTC) services and support for family caregivers of people with dementia, such as China [29]. Furthermore, research institutes in various countries have conducted extensive research investigating interventions for dementia caregivers' health issues.…”
Section: Discussionmentioning
confidence: 99%